Changing Physician Practice of Physical Activity Counseling - Eckstrom, Elizabeth (Blackwell Science Inc, 1999)
We conducted a prospective controlled trial to determine whether an educational intervention could improve resident physician self-efficacy and counseling behaviors for physical activity and increase their patients’ reported activity levels. Forty-eight internal medicine residents who practiced at a Department of Veterans Affairs hospital received either two workshops on physical activity counseling or no intervention. All residents completed questionnaires before and 3 months after the workshops. The 21 intervention physicians reported increased self-efficacy for counseling and increased frequency of counseling compared with the 27 control physicians. Approximately 10 patients of each resident were included in the study and surveyed before and 6 months after the intervention. Of 560 patients, 465 (83%) returned both questionnaires. Following the intervention, there were no significant differences between patients of intervention and control physicians on any outcome measures. We conclude that educational interventions can improve physicians’ reported self-efficacy of physical activity counseling but may not increase patient physical activity levels. Alternative approaches that emphasize overcoming the substantial barriers to exercise in chronically ill outpatients clearly will be important for facilitating changes in physical activity.